Impact of Emissions Intensive Industries And Financial Distress On Voluntary Carbon Emission Disclosure - Rahmadhani, Sari; Indriyani, Rahayu (UNIVERSITAS NEGERI SURABAYA, 2019)
This study aims to examine factors affecting voluntary disclosure of carbon emissions. Factors affecting the disclosure of voluntary carbon emissions consist of emissions-intensive industries and financial distress represented by leverage. The sampling method used is pruposive sampling with the following criteria, companies that have received a corporate governance rating index during the observation period and published annual reports during the observation period (2013-2016). Based on the corporate governance index determined 66 sampled research. The analysis technique used to test the hypothesis of this research is multiple linear regression analysis. The results of this study indicate that emissions-intensive industries have a significant positive impact on the disclosure of voluntary carbon emissions. Financial distress has a significant negative impact on voluntary carbon disclosure.